Toxic Income as a Trigger of Climate Change - Falconí, Fander (2019)
The rate of CO2 emissions concentration in the atmosphere increases the likelihood of significant impacts on humankind and ecosystems. The assumption that permissible levels of greenhouse gas emissions cannot exceed the global average temperature increase of 2 °C in relation to pre-industrial levels remains uncertain. Despite this uncertainty, the direct implication is that enormous quantities of fossil fuels have, thus far, wrongly been counted as assets by hydrocarbon firms as they cannot be exploited if we want to keep climate under certain control. These are the so-called “toxic assets”. Due to the relationship among CO2 emissions, GDP, energy consumption, and energy efficiency, the concept of toxic assets can be transferred to toxic income, which is the income level that would generate levels of CO2 emissions incompatible with keeping climate change under control. This research, using a simulation model based on country-based econometric models, estimated a threshold for income per capita above which the temperature limit of 2 °C would be surpassed. Under the business as usual scenario, average per capita income would be $14,208 (in constant 2010 USD) in 2033; and under the intervention scenario, which reflects the commitments of the COP21 meeting held in Paris in December 2015, the toxic revenue would be $13,433 (in constant 2010 USD) in 2036.